Removal of tetracycline from aqueous solutions using nanoscale zero valent iron and functional pumice modified nanoscale zero valent iron - Guler, Ulker Asli (Journal of Environmental Engineering and Landscape Management, 2017)
Nanoscale zero valent iron (nZVI) and functional pumice modified nanoscale zero valent iron (P-nZVI) were successfully synthesized and used for the removal of tetracycline (TC). These materials were characterized by SEM, TEM, XRD, FTIR, BET. Different factors such as the mass ratio, dosage of adsorbent, ph, initial TC concentration and temperature were investigated. Based on these results; a possible removal mechanism was proposed including TC adsorption and TC reduction via oxidation of Fe0 to Fe3+. In addition, isotherm and thermodynamic parameters were applied to the equilibrium data. The maximum adsorption capacity of TC by nZVI and P-nZVI was 105.46 mg/g and 115.13 mg/g, respectively. Adsorption and reduction kinetics were examined for the TC removal process. The pseudo-second-order model and pseudo-first-order model was observed for adsorption and reduction process, respectively. Finally, more than 90% of TC from aqueous solutions was removed by nzvi and P-nZVI.First published online: 28 Nov 2016